Science Processing Skill Improvement Through POGIL (Process Oriented Guided Inquiry Learning) Learning Model - Mohamad Tofan Hanib; Suhadi Suhadi; Sri Endah Indriwati (Pascasarjana Universitas Negeri Malang (UM), 2017)
Abstract: This research is aimed to investigate the students’ improvement through POGIL (Process Oriented Guided Inquiry Learning) learning model. It is a classroom action reesarch. The research was taken under two cycles of four steps (planning, implementing, observing, and reflecting). The data was collected through observation, interviews, and questionnaires. The result of the research shows that there is a significant improvement upon the students’ science processing skill through POGIL learning model. Key Words: students’ science processing skill, Process Oriented Guided Inquiry Learning, POGILAbstrak: Penelitian ini bertujuan untuk mengetahui perkembangan siswa melalui pembelajaran POGIL (Process Oriented Guided Inquiry Learning). Penelitian ini adalah penelitian tindakan kelas. Penelitian dilakukan sebanyak 2 siklus dari 4 langkah (perencanaan, pelaksanaan, pengamatan, dan refleksi). Data dikumpulkan melalui observasi, wawancara, dan kuesioner. Hasil penelitian menunjukkan bahwa ada peningkatan yang signifikan terhadap keterampilan proses sains siswa melalui model pembelajaran POGIL.Kata kunci: kemampuan proses sains siswa, Proses Oriented Guided Inquiry Learning, POGIL